The impact of different acidic conditions and food substrates on Listeria monocytogenes biofilms development and removal using nanoencapsulated carvacrol - Jina, Yammine (2024)
Listeria monocytogenes biofilms present a significant challenge in the food industry. This study explores the impact of different acidic conditions of culture media and food matrices on the development and removal of biofilms developed on stainless steel surfaces by wild-type (WT) L. monocytogenes strains as well as in two mutant derivatives, ΔsigB and ΔagrA, that have defects in the general stress response and quorum sensing, respectively. Additionally, the study investigates the efficacy of nanoencapsulated carvacrol as an antimicrobial against L. monocytogenes biofilms developed in Tryptic Soy Broth (TSB) culture media acidified to different pH conditions (3.5, 4.5, 5.5, 6.5), and in food substrates (apple juice, strained yogurt, vegetable soup, semi-skimmed milk) having the same pH levels. No biofilm formation was observed for all L. monocytogenes strains at pH levels of 3.5 and 4.5 in both culture media and food substrates. However, at pH 5.5 and 6.5, increased biofilm levels were observed in both the culture media and food substrates, with the WT strain showing significantly higher biofilm formation (3.04–6.05 log CFU cm−2) than the mutant strains (2.30–5.48 log CFU cm−2). For both applications, the nanoencapsulated carvacrol demonstrated more potent antimicrobial activity against biofilms developed at pH 5.5 with 2.23 to 3.61 log reductions, compared to 1.58–2.95 log reductions at pH 6.5, with mutants being more vulnerable in acidic environments. In food substrates, nanoencapsulated carvacrol induced lower log reductions (1.58–2.90) than the ones in TSB (2.02–3.61). These findings provide valuable insights into the impact of different acidic conditions on the development of L. monocytogenes biofilms on stainless steel surfaces and the potential application of nanoencapsulated carvacrol as a biofilm control agent in food processing environments.